IMPLEMENTASI KEBIJAKAN E-GOVERNMENT PADA SISTEM INFORMASI ADMINISTRASI KEPENDUDUKAN DI KOTA BANDUNG - Yani Andriyani Kautsar; Djadja Saefullah (Scientia Regendi, 2022)
ABSTRACT This thesis is the result of research to describe the extent of the policy implementation of e-Goverment in the population administration information system in Bandung City, which is one of the task in the field of public service administration. Through this thesis, it will try to identivy the process and factors that affect the policy implementation of e-Goverment in the population administration information system in Bandung City, and formulate a solution for handling these problems by referring to relevant theory, in an effort to contribute ideas to the development of science and provide informatiob materials to local government in taking further politics. The arrangement of the thesis is based on the field research in order to gather primary data and library research in gathering secondary data. This research conductes a qualitative approach to data collecting technique. Based on research, it may conclude that aspects of communication, resources, disposition and bureaucratic structure have a major impact on implementation of e-Government in the population administration information system in Population and Civil Registry Office of City Government of Bandung. Key words: Policy Implementation, e-Government, The Population administration information System